ChemInform Abstract: Synthesis of Fluorinated Tricyclic Scaffolds by Intramolecular [2 + 2] Photocycloaddition Reactions. Issue 11 (8th March 2013) - Fort, Diego A.; Woltering, Thomas J.; Nettekoven, Matthias; Knust, Henner; Bach, Thorsten
Abstract The title reaction using fluorinated alkene substrates allows the access to various tricyclic systems.